Theoretical study of the photophysical processes of a styryl‐bodipy derivative eliciting an AND molecular logic gate response. Issue 16 (19th April 2019) - Tzeli, Demeter; Petsalakis, Ioannis D.; Theodorakopoulos, Giannoula
Abstract: We study, via density functional theory and time dependent DFT calculations, the photophysical processes of a styryl‐bodipy derivative, which acts as a three metal‐cation‐receptor fluorophore in order to (a) gain information on the appropriate computational approach for successful prediction of molecular logic gate candidates, (b) rationalize the available experimental data and (c) understand how the given combination of three different receptors with the BODIPY fluorophore presents such interesting optoelectronic responses. The fluorophore (1 ), its monometallic complexes (1‐Ca 2+, 1‐Zn 2+, and 1‐Hg 2+ ), and its trimetallic complex (2 ) are studied. The calculated λmax values for absorption and emission are in excellent agreement with experimental data. It was found that the observed quenching of emission of 1 and of the monometallic complexes is attributed to the fact that their first excited state is a charge‐transfer state whereas this does not happen for the complex 2 . It should be noted that for the correct ordering of the excited states, the inclusion of corrections to the excitation energies for nonequilibrium solvent effects is required; while in the case of 1‐Ca 2+, the additional explicit inclusion of the solvent is necessary for the quenching of the emission spectra. Abstract : A three‐receptor fluorophore, which has been characterized as a three input AND molecular logical gate candidate, is studied via DFT calculations. The quenching mechanism of the emission of the single fluorophore and its monometallic complexes (1‐Ca 2+, 1‐Zn 2+, 1‐Hg 2+ ) is revealed, while the emission of the trimetallic complex of fluorophore is retained. Correct description of nonequilibrium solvent effects is paramount for accuracy, and in the case of 1‐Ca 2+ explicit inclusion of the solvent is required.